2010
DOI: 10.1007/s10900-010-9321-y
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use, Recreational Travel, and HIV Risk Behaviors in Men Who Have Sex With Men

Abstract: Previous studies have documented higher rates of HIV risk behavior in gay and bisexual men traveling for leisure. Most of these studies collected data in high-risk tourist areas known for promoting alcohol and other substance use. The present study sampled a broader range of men by collecting data at a Gay Pride celebration, and asking participants about vacation experiences over the past 12 months. We also collected information about men's use of the Internet to find sexual partners before they traveled. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 43 publications
5
39
0
1
Order By: Relevance
“…The internet permits the creation of social and sexual networks that facilitate contact and the security of having a sexual encounter. In some studies (Benotsch et al 2011) men who used the internet to set up dates before travelling reported significantly more sexual partners and were significantly more likely to report having sex with a new partner. Interventions designed to reduce risk behaviour in this population are needed.…”
Section: Conclusion Regarding Sex Abroad and Buying And Selling Sexmentioning
confidence: 99%
“…The internet permits the creation of social and sexual networks that facilitate contact and the security of having a sexual encounter. In some studies (Benotsch et al 2011) men who used the internet to set up dates before travelling reported significantly more sexual partners and were significantly more likely to report having sex with a new partner. Interventions designed to reduce risk behaviour in this population are needed.…”
Section: Conclusion Regarding Sex Abroad and Buying And Selling Sexmentioning
confidence: 99%
“…These men who sought partners before travel were more likely to have a new sexual partner and report more sexual partners during travel, compared with survey respondents who did not use the Internet to seek out partners before travel. 7 Similar patterns of utilising online social networking platforms to identify potential sexual partners at the travel destination before travel have also been observed in Asia and Africa. In Vietnam, Nguyen et al found that of the 41% of MSM who reported a new or casual sexual partner while abroad, approximately half found their partner from the Internet.…”
Section: Increasing Access To Sex Partners During Travel Through Onlimentioning
confidence: 70%
“…7 This risk may be further amplified when the reason for travel is to attend group sex events; men who attended these events were more likely to report having multiple sex partners, engaging in CAI with sexual partners of unknown HIV status, and engaging in alcohol and substance use. 9,10,12 perceived to be higher or lower HIV risk is not well understood; studies have been limited given the inherent challenges of sampling the particular MSM that travel more than others.…”
Section: Patterns Of Behaviour During Travelmentioning
confidence: 99%
See 1 more Smart Citation
“…An assumption was accepted that the LGBT environment possesses a significant share in the penetration of the internet (Benotsch et al, 2011). On the basis of the author's own research and a review of literature in the area of research issues, an attempt was made to formulate general conclusions concerning (expected) behaviours and tourist preferences of the LGBT environment in Poland.…”
Section: Methodsmentioning
confidence: 99%